Explaining reshoring in the context of Asian competitiveness: evidence from a Swedish firm. Issue 2 (21st March 2019) - Fjellstrom, Daniella; Fang, Tony; Chimenson, Dina
Abstract : Purpose: The purpose of this paper is to arrive at a different understanding of reshoring in Asia vis-à-vis the Western context of competitiveness, through a case study of the Swedish company FM Mattsson. Design/methodology/approach: Empirical studies with semi-structured interviews have been conducted both in Sweden and China to gain an in-depth understanding of the case company's reshoring activities. Findings: The findings point at reshoring as a competitive means to respond to the dynamics of internal (firm-specific) and external (country-specific) factors. Reshoring comes as a dynamic process by reshuffling resources inside and outside of the firm that strives for continuous competitiveness. Organizations need to meet the challenges of changing environment, especially the dynamic business competition in Asia, and reshoring is a way. Originality/value: This paper contributes to the literature by perceiving reshoring as a dynamic process of competitiveness development. Reshoring is not seen as one-off short-term decision-making on cost and location but as a long-term process in response to the dynamic internal and external challenges ahead.